2019
DOI: 10.1186/s12884-019-2653-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal healthcare services use in Mwanza Region, Tanzania: a cross-sectional baseline survey

Abstract: BackgroundImproving maternal health by reducing maternal mortality/morbidity relates to Goal 3 of the Sustainable Development Goals. Achieving this goal is supported by antenatal care (ANC), health facility delivery, and postpartum care. This study aimed to understand levels of use and correlates of uptake of maternal healthcare services among women of reproductive age (15–49 years) in Mwanza Region, Tanzania.MethodsA cross-sectional multi-stage sampling household survey was conducted to obtain data from 1476 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…40 41 This finding might be explained by the fact that health-seeking behaviour among women has been associated with the level of education, which has been indicated as the major determinant of maternal health services utilisation in most previous studies. 16 [49][50][51] Also, it has been shown that most households with low socioeconomic status in Tanzania and other SSA countries also have lower educational attainment. 38 Therefore, achieving equalities in ANC utilisation should also target education policies by considering profound improvements for women from poor households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 41 This finding might be explained by the fact that health-seeking behaviour among women has been associated with the level of education, which has been indicated as the major determinant of maternal health services utilisation in most previous studies. 16 [49][50][51] Also, it has been shown that most households with low socioeconomic status in Tanzania and other SSA countries also have lower educational attainment. 38 Therefore, achieving equalities in ANC utilisation should also target education policies by considering profound improvements for women from poor households.…”
Section: Discussionmentioning
confidence: 99%
“…8 14 15 The socioeconomic factors such as maternal age, education, residence, wealth and occupation were much discussed as the major influence of ANC utilisation that disproportionally favours wealthier women. [16][17][18] Although little is known about the contributions of these factors to the inequalities in ANC utilisation in Tanzania, they have been well assessed and discussed in other developing countries such as in South Asian countries. [19][20][21] Previous studies in the later region highlight wealthrelated inequalities as the major driver of ANC utilisation in favour of wealthier women.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Details of the study settings have been reported elsewhere [ 17 ]. Briefly, this study was conducted in Mwanza Region, which is in the northern part of Tanzania bordering Lake Victoria.…”
Section: Methodsmentioning
confidence: 99%
“…Many demographic factors have been positively associated with attending postpartum visits, including higher socioeconomic status (Upadhyai & Gupta, 2019), higher educational status of mothers or their partners (Kifle et al, 2017;Sakeah et al, 2018;Upadhyai & Gupta, 2019), older age (Sakeah et al, 2018), and having a religious affiliation (Kifle et al, 2017). Many health-related factors have also been associated with attending postpartum visits, including a history of attending prenatal care (Sakeah et al, 2018;Upadhyai & Gupta, 2019), giving birth at a health facility (Orwa et al, 2019), having a cesarean birth (Upadhyai & Gupta, 2019), and knowledge of pregnancy complications or perception of a postpartum health problem (Kifle et al, 2017).…”
Section: Available Knowledgementioning
confidence: 99%